Chlamydophila pneumoniae infection and its contribution to atherosclerosis (literature review) - A. L. Poznyak; S. N. Sidorchuk; A. V. Tarasov (Журнал инфектологии)
The prevalence of atherosclerosis and associated diseases and complications creates preconditions to study them in the framework of the common pathological process. This review presents the modern data on the role of Chlamydophila pneumoniae infections, as well as data about the influence of the factors of systemic and local inflammationat the infection to the development of atherosclerosis.